KAJIAN STATISTIK UKURAN BESAR BUTIR SEDIMEN DAN KAITANNYA DENGAN VARIABILITAS IKLIM MUSIMAN DAN TAHUNAN DI MUARA GEMBONG, TELUK JAKARTA - Taufik R. Syachputra; Ivonne M. Radjawane; Rina Zuraida (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Climate variability affects the properties of marine sediments. One of the sediment properties affected by climate is the grain size. This study is aimed to test the relation between sediment grain size and climate variability using sediment core GM01-2010-TJ22 that was acquired off Muara Gembong, which is part of Citarum river mouth. The samples were acquired in 2010 onboard RV. Geomarin I by Marine Geological Institute (MGI). Grain size analysis was conducted by Mastersizer 2000. The mean grain size is presented in time series for the 2001-2010 period. Then, the grain size sediment sample was correlated statistically with the seasonal (monsoon), annual, and interannual (El Niño/La Niña and Dipole Mode) phenomena. Data verification was conducted using secondary data of sea surface temperature from satellite images near the sediment sampling location and rainfall data in Bekasi. The verification result shows an increase in precipitation rate downriver of Citarum River followed by the decrease of sea surface temperature and larger grain size. The results using statistical test show that change of sediment sample`s grain size in Muara Gembong have significant correlation with Multivariate of ENSO (El Niño Southern Oscillation) Index (MEI), Ocean Niño Index (ONI), Dipole Mode Index (DMI) and Australian Monsoon Index (AUSMI). This result shows that sediment grain size can potentially be used to identify climate variability in Jakarta Bay.